MENINGKATKAN KEMAMPUAN BERBEDAK MELALUI PENDEKATAN KOOPERATIF PADA ANAK TUNAGRAHITA SEDANG - Delwita - Imna (Jurnal Penelitian Pendidikan Khusus, 2012)
Intention of this research is 1) Description process execution of study to increase ability of have powder  and 2) Proving do approach of co-operative can improve ability of have powder to  child of tunagrahita class is D.III /C1 in SLB Syech Muhammad Saad Limapuluh Kota. Type Research the used is classroom  action  research. Data obtained to through and observation of tes. Later then analysed qualitative and is quantitative. Result of research indicate that 1) study process in improving ability of have powder  by approach of co-operative with two cycle. Each cycle early with activity of planning, execution (activity early, nucleus;core and is final), observation, analysis and and refleksi 2) Result of from study with approach of co-operative to ability of have powder to mount. Matter is proven: before treatment of ability of have child powder namely: Wt equal to ( 30,6%), ability of Fn ( 27,8%), ability of Mn ( 16,7%). Cycle of I have mounted namely Wt equal to ( 72,2%), Fn equal to ( 66,7%) and Mn is ( 55,6%). While at cycle of II progressively mount, where Wt ( 94,4%), Fn ( 86,1%). Thereby, can be concluded that approach of co-operative can assist to improve ability of have tunagrahita child of  powder. Suggesting on the side of school, researcher and teacher hereinafter to be able to use approach of co-operative in improving other ability